36.2k views
4 votes
5p−m=10 answer my question

User Fangxin
by
6.3k points

2 Answers

1 vote

Answer:

m = -10 + 5p

Explanation:

5p − m = 10

subtract 5p from both sides:

5p − m - 5p = 10 - 5p

simplifiy:

-m = 10 - 5p

divide -1 to both sides

m = -10 + 5p

m = -10 + 5p

===========

User Jpostdesign
by
5.8k points
6 votes

I'm going to assume you want solve for m.

Steps to solve:

5p − m = 10

~Subtract 5p to both sides

-m = 10 - 5p

~Divide -1 to everything

m = -10 + 5p

Best of Luck!

User Zahid Hasan Emon
by
5.4k points